Immunogenicity and safety of a 13-valent pneumococcal conjugate vaccine administered to older infants and children naïve to pneumococcal vaccination. Issue 14 (30th March 2015) - Wysocki, Jacek; Brzostek, Jerzy; Szymański, Henryk; Tetiurka, Bogusław; Toporowska-Kowalska, Ewa; Wasowska-Królikowska, Krystyna; Sarkozy, Denise A.; Giardina, Peter C.; Gruber, William C.; Emini, Emilio A.; Scott, Daniel A.
Highlights Some children may not receive pneumococcal conjugate vaccine (PCV) as infants. PCV13 was evaluated in pneumococcal vaccine-naïve children aged 7 months to 5 years. Age-specific "catch-up" vaccination schedules were evaluated. The proportion of immunological responders ranged from 88% to 100% for all 13 serotypes. PCV13 was generally well-tolerated; trend for greater tenderness in older subjects.